Taṭbīq aṭ-Ṭarīqah al-Istijābah al-Jasadiyyah al-Kulliyyah li at-Tarqiyyati Quwwah Istiżkāri aṭ-ṭalabah fii Ta‘allumi al-Mufradāti al-Arabiyyati - Nissa Bela Nurussalma; 'Aabidah Ummu 'Aziizah; Mohammad Syaifuddin; Muqowim; Muhammad Fahri Kholid (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2022)
This research is important to do because the effectiveness of learning in Indonesian informal educational institutions, especially Student's Education Parks is still quite low. This study aims to determine the effect of Total Physical Response (TPR) on improving Arabic vocabulary memory for TPQ students at the Nurul 'Ilmi Mosque in Semarang City and find new variations in learning methods for TPQ students who have various ages at each level. This research uses Non Equivalent Control Group Design. The participants in this study were 30 students at the TPQ Nurul 'Ilmi Mosque, Semarang City. The data analysis technique used is quantitative data analysis. The findings in this study stated that TPR was proven to be effective in improving the memory of Arabic vocabulary in the TPQ students of the Nurul 'Ilmi Mosque in Semarang City in terms of response indicators, processes and results. This can be seen from the difference in the results of the comparison test between the control class and the experimental class with an N-Gain of 3.86 which indicates a significant level of gain in the high category. This TPR method provides an alternative for TPQ teachers in providing activities in learning that are more interesting than usual so that they can spur the development of various student's abilities and the creativity of TPQ teachers in innovating in each lesson. Keywords: Total Physical Response, Student’s Memory, Learning Arabic Vocabulary ملخص هذا البحث مهم للقيام به لأن فعالية التعلم في المؤسسات التعليمية غير الرسمية الإندونيسية ، وخاصة حدائق تعليم الطلبة لا تزال منخفضة للغاية . تهدف هذه الدراسة إلى تحديد تأثير الاستجابة البدنية الكلية (TPR) على تحسين ذاكرة المفردات العربية لطلبة TPQ في مسجد نورل العلم في مدينة سيمارانج والعثور عليها جديد الاختلافات في طرق التعلم لطلبة TPQ الذين لديهم أعمار مختلفة في كل مستوى. يستخدم هذا البحث تصميم مجموعة التحكم غير المكافئ. كان المشاركون في هذه الدراسة 30 طالبا في مسجد TPQ Nurul 'Ilmi ، مدينة سيمارانج. تقنية تحليل البيانات المستخدمة هي تحليل البيانات الكمية. ذكرت النتائج في هذه الدراسة أن TPR أثبتت فعاليتها في تحسين ذاكرة المفردات العربية في أطفال TPQ من مسجد نورالعلم في مدينة سيمارانج من حيث مؤشرات الاستجابة والعمليات والنتائج. يمكن ملاحظة ذلك من خلال الاختلاف في نتائج اختبار المقارنة بين فئة التحكم والفئة التجريبية مع N-Gain 3.86 مما يشير إلى مستوى كبير من الكسب في الفئة العالية. توفر طريقة TPR هذه بديلاً لمعلمي TPQ في توفير أنشطة في التعلم أكثر إثارة للاهتمام من المعتاد حتى يتمكنوا من تحفيز تنمية قدرات الطلبة المختلفة وإبداع معلمي TPQ في الابتكار في كل درس. الكلمات الاساسية: الاستجابة الجسدية الكلية، ذاكرة الطالب، تعلم المفردات العربية